An analysis of the impact of an e-classroom environment on the social, cognitive and affective elements of student work practices - Falloon, Garry Wayne (Curtin University, 2004)
This thesis documents the findings of an intrinsic case study examining the impacts of a digital or e-classroom environment on the social, affective, and cognitive development of a group of 33 year 5 and 6 students, in an urban primary school in Northland, New Zealand.It examines the manner in which the e-classroom concept was developed and implemented, the rationale behind its development, and the role of key players in this process. It further examines the impact of this environment on student work processes and practices, and identifies the unique blend of teacher philosophy, curriculum design and organisation, and computer application that comprised the learning environment for these students.Results of this study indicate particular issues associated with the successful operation of this e-classroom. These issues relate to such aspects as difficulties in managing and monitoring student progress when engaged in the multiplicity of learning tasks enabled by such an environment, the importance of student group composition and selection, the limitations of computers in supporting important knowledge development, and the manner in which students interact with and manipulate the features of software.The thesis concludes by presenting an analysis of the impact that these, and other vital areas of student engagement with computers, have on the effectiveness of utilising technological resources in this manner. It presents a series of recommendations for changes to improve the effectiveness of the learning environment in this e-classroom, and identifies a series of considerations for other schools considering undertaking similar initiatives.